(3CSGdjH GdHMK GdYdej hJWHjbGJI aj GdJNWjW hGdGOGQIs - (3QHMj eUWai(B, (3YdjGfs; (3YKeGf eMeO Zfje hBNQhf(B, s ((3YeGf(B:s (3OGQ UaGA(B,s, 2008)
(3GdHMK GdYdej, efGgL GdHMK GdYdej, NWhGJ GdHMK GdYdej, WQb hCOhGJ LeY GdHjGfGJ, GdYjfGJ(B/ (3YQV hJMdjd GdHjGfGJ, JhKjb GdHMK GdYdej, GdGfJQfjJ hGdHMK GdYdej, cJGHI JbQjQ GdHMK GdYdejs
(3HHdjhZQGajG(B: (3U(B.325s
Keywords: (3GdGfJQfjJs; (3GdefGgLs; (3WQb GdHMKs